2020
DOI: 10.1137/19m1248583
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Recovery for the 2 Dimensional Navier--Stokes Equations via Continuous Data Assimilation

Abstract: We study a continuous data assimilation algorithm proposed by Azouani, Olson, and Titi (AOT) in the context of an unknown Reynolds number. We determine the large-time error between the true solution of the 2D Navier-Stokes equations and the assimilated solution due to discrepancy between an approximate Reynolds number and the physical Reynolds number. Additionally, we develop an algorithm that can be run in tandem with the AOT algorithm to recover both the true solution and the Reynolds number (or equivalentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 65 publications
(116 reference statements)
0
55
0
Order By: Relevance
“…This is often a difficult task, as such parameters are difficult to measure and/or noise in the measurement process precludes identifying the parameters exactly. Motivated by [9], we develop a robust algorithm that estimates multiple parameters in a partial differential equation (PDE) when those parameters can be written as coefficients of the various terms in the PDE. As the current algorithm relies on the feedback control data assimilation mechanism introduced in [1], we simultaneously identify not only the parameters of the system, but also obtain the dynamical state of the system based on reduced observations of the true state.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is often a difficult task, as such parameters are difficult to measure and/or noise in the measurement process precludes identifying the parameters exactly. Motivated by [9], we develop a robust algorithm that estimates multiple parameters in a partial differential equation (PDE) when those parameters can be written as coefficients of the various terms in the PDE. As the current algorithm relies on the feedback control data assimilation mechanism introduced in [1], we simultaneously identify not only the parameters of the system, but also obtain the dynamical state of the system based on reduced observations of the true state.…”
Section: Introductionmentioning
confidence: 99%
“…All of these extensions have broadened the applicability of the AOT algorithm but rely on the accurate representation of the underlying model parameters. Recently, data assimilation for an imperfect model has been considered in different contexts [15,9,18]. It is rigorously established for two distinct settings that when a parameter of the system is unknown, that error in the assimilation will still converge up to the error in a single unknown parameter (see [9,18]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover our studies are carried out to a similar high degree of numerical precision as found in [FJJT18]. We refer the reader to [ANLT16,FET17,DLMB18,CHL18] for various other studies in the context of turbulent flows such as how one can leverage the nudging scheme to infer unknown parameters of the flow. In [BM17,IMT18,MT18] analytical studies on the various modes of synchronization of the algorithm (1.2) and on certain variants on its numerical discretization were carried out.…”
Section: Introductionmentioning
confidence: 99%
“…This seemingly minor change had profound impacts, and the authors of [5] were able to prove that using only sparse observations, the CDA algorithm applied to the 2D Navier-Stokes equations converges to the correct solution exponentially fast in time, independent of the choice initial data. This stimulated a large amount of recent research on the CDA algorithm; see, e.g., [3,6,7,10,11,13,17,18,19,20,21,22,27,31,30,35,40,41] and the references therein. The recent paper [15] showed that CDA can be effectively used for weather prediction, showing that it can indeed be a powerful tool on practical large scale problems.…”
mentioning
confidence: 99%